2019
DOI: 10.1589/jpts.31.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased functional residual capacity on finger-floor distance in healthy young adults

Abstract: [Purpose] To investigate the effect of increased functional residual capacity on the finger-floor distance and to assess spinal curvature in the sagittal plane using the Spinal Mouse in healthy young participants. [Participants and Methods] Thirty-nine healthy volunteers (age=21.2 ± 0.8 years) participated in this study. The finger-floor distance was used to measure trunk flexion and was recorded at the resting expiration level and at 2 different functional residual capacity levels: 1,000 and 2,000 ml air inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Our previous study demonstrated that increased functional residual capacity might decrease the active range of thoracic axial rotation 5) and a finger-floor distance 6) in healthy young adults, though the causes and mechanisms of poor thoracic mo-bility in patients with COPD are complicated. These studies had limitations that required solving, i.e., IC was not measured using spirometry.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that increased functional residual capacity might decrease the active range of thoracic axial rotation 5) and a finger-floor distance 6) in healthy young adults, though the causes and mechanisms of poor thoracic mo-bility in patients with COPD are complicated. These studies had limitations that required solving, i.e., IC was not measured using spirometry.…”
Section: Introductionmentioning
confidence: 99%